UDP-Lite Enhancement Through Checksum Protection. (March 2017) - Suherman,; Abdurrahman, H; Sitompul, O S; Mubarakah, N
Abstract: UDP drops packet when checksum bits in header does not match the checksum bits calculated from the receive data. UDP-Late improves UDP by using partial checksum coverage. However, checksum error in both UDP and UDP-Lite headers is potentially leading to wrong decision in dropping part(s) of packet. This article proposes protocol to avoid the problem by using Forward Error Correction (FEC) code to protect checksum bits. The evaluation results show that the number of the received bytes increases up to 0.3% compared to UDP-Lite, which leads to 3 dB increment of the received image quality.